Ruins of a building, Kingston, Norfolk Island, ca. 1970 - Stacey, Wes (Wesley), 1941-2023. (1968)
Depicting rubble construction, yard.
Part of the Wes Stacey archive of architectural photographs, 1968-1972.
Catalogue record generated as part of a batch load.
Title from acquisitions document, see file NLA09/703.
Wes Stacey reference number: 2 07 6.
Also available online
Keywords: Stone buildings -- Norfolk Island -- Kingston -- Photographs; Excavations (Archaeology) -- Norfolk Island -- Kingston -- Photographs; Kingston (Norfolk Island) -- Buildings, structures, etc. -- Photographs